Sleep disturbances and psychological well-being among military medical doctors of the Swiss Armed Forces: study protocol, rationale and development of a cross-sectional and longitudinal interventional study - Dena Sadeghi-Bahmani; Dena Sadeghi-Bahmani; Viola Rigotti; Zeno Stanga; Zeno Stanga; Undine E. Lang; Rebecca K. Blais; Michelle L. Kelley; Serge Brand; Serge Brand; Serge Brand (Frontiers Media S.A., 2024)
BackgroundCompared to civilians and non-medical personnel, military medical doctors are at increased risk for sleep disturbances and impaired psychological well-being. Despite their responsibility and workload, no research has examined sleep disturbances and psychological well-being among the medical doctors (MDs) of the Swiss Armed Forces (SAF). Thus, the aims of the proposed study are (1) to conduct a cross-sectional study (labeled 'Survey-Study 1') of sleep disturbances and psychological well-being among MDs of the SAF; (2) to identify MDs who report sleep disturbances (insomnia severity index >8), along with low psychological well-being such as symptoms of depression, anxiety and stress, but also emotion regulation, concentration, social life, strengths and difficulties, and mental toughness both in the private/professional and military context and (3) to offer those MDs with sleep disturbances an evidence-based and standardized online interventional group program of cognitive behavioral therapy for insomnia (eCBTi) over a time lapse of 6 weeks (labeled 'Intervention-Study 2').MethodAll MDs serving in the SAF (N = 480) will be contacted via the SAF-secured communication system to participate in a cross-sectional survey of sleep disturbances and psychological well-being ('Survey-Study 1'). Those who consent will be provided a link to a secure online survey that assesses sleep disturbances and psychological well-being (depression, anxiety, stress, coping), including current working conditions, job-related quality of life, mental toughness, social context, family/couple functioning, substance use, and physical activity patterns. Baseline data will be screened to identify those MDs who report sleep disturbances (insomnia severity index >8); they will be re-contacted, consented, and randomly assigned either to the eCBTi or the active control condition (ACC) ('Intervention-Study 2'). Individuals in the intervention condition will participate in an online standardized and evidence-based group intervention program of cognitive behavioral therapy for insomnia (eCBTi; once the week for six consecutive weeks; 60-70 min duration/session). Participants in the ACC will participate in an online group counseling (once the week for six consecutive weeks; 60-70 min duration/session), though, the ACC is not intended as a bona fide psychotherapeutic intervention. At the beginning of the intervention (baseline), at week 3, and at week 6 (post-intervention) participants complete a series of self-rating questionnaires as for the Survey-Study 1, though with additional questionnaires covering sleep-related cognitions, experiential avoidance, and dimensions of self-awareness.Expected outcomesSurvey-Study 1: We expect to describe the prevalence rates of, and the associations between sleep disturbances (insomnia (sleep quality); sleep onset latency (SOL); awakenings after sleep onset (WASO)) and psychological well-being among MDs of the SAF; we further expect to identify specific dimensions of psychological well-being, which might be rather associated or non-associated with sleep disturbances.Intervention-Study 2: We expect several significant condition-by-time-interactions. Such that participants in the eCBTi will report significantly greater improvement in sleep disturbances, symptoms of depression, anxiety, stress reduction both at work and at home (family related stress), and an improvement in the overall quality of life as compared to the ACC over the period of the study.ConclusionThe study offers the opportunity to understand the prevalence of sleep disturbances, including factors of psychological well-being among MDs of the SAF. Further, based on the results of the Intervention-Study 2, and if supported, eCBTi may be a promising method to address sleep disturbances and psychological well-being among the specific context of MDs in the SAF.